Relationship Between Menstruation and Nutritional Status to Anemia in Female High School Students in Mentawai Islands, 2018 - Elizabeth Ameilia Dewi; Christianus Heru Setiawan; Angela Kurniadi; Tommy Nugroho Tanumihardja (Sanata Dharma University, 2025)
Anemia is a significant health concern, especially among adolescent females in Indonesia. Menstruation and poor nutrition are major contributors to anemia, since menstruation leads to red blood cell loss and poor nutrition hinders production. This study examines the relationship between menstrual characteristics, nutritional status, and anemia among high school female students in Muara Siberut Village, Mentawai Islands. This cross-sectional observational study involved 97 female high school students. We assessed nutritional status using BMI percentiles and categorized menstrual characteristics according to standard gynecological classifications. Anemia was diagnosed via hemoglobin measurements using a digital hemoglobinometer. Statistical analyses (p0.05) with odds ratio (OR) and 95% confidence interval (CI) utilized Chi-square or Fisher’s exact tests to explore associations between menstrual characteristics, nutritional status, and anemia. No significant correlation was observed between nutritional status and anemia (p=0.394). Conversely, a significant correlation was found between the menstrual cycle and anemia (p=0.023) as well as between menstrual length and anemia (p=0.017). Furthermore, a subgroup analysis revealed individuals with a normal menstrual cycle were at a higher risk of experiencing anemia compared to those with oligomenorrhea (OR=4, 95%CI=0.988–16.199). Additionally, the results indicated that individuals with normal menstrual length were at a higher risk of experiencing anemia compared to those with hypomenorrhea (OR=4.624, 95%CI=1.174–18.202). This study provides valuable insights into the predictors of anemia among female adolescents, emphasizing the need for targeted health education and interventions.